Penerapan Thought Stopping (TS) dan Assertive Trainning (AT) terhadap Kecemasan Warga Binaan Sebelum Bebas di Lembaga Perempuan Kelas II A Pekanbaru - Usraleli Usraleli; Erni Forwaty (Universitas Batanghari Jambi, 2022)
The life that a female citizen lives in prison makes her face psychological problems such as loss of family, loss of self-control, model loss, and loss of support. It can also lead to anxiety among female assisted people associated with the negative stigma that still exists around the community. People who still look negative about the status of ex-citizens. The purpose of this study was determine the factors that affect the anxiety of female assisted people before the liberation period at the Institute of Special Education Children Pekanbaru. This research method is done by using Cross sectional method. The population of this study is all female assisted citizens in Special Education Institution Anak Pekanbaru children who will be free in the year 2017 as many as 30 people, using a questionnaire that has been standardized and has been tested the validity. Based on the results of this study most of the female assisted people experience mild anxiety as much as 66,7%. The results of this study found no relationship that affects the anxiety of female assisted women before the liberation period. The conclusion of this research is the majority of female assisted people in Lemabag Special Education of Children of Pekanbaru have mild anxiety and from four factors studied, one factor that influence the anxiety of female assisted people is social environment factor with environment category is not conducive. Suggestions for the targeted citizens is to increase confidence and hone skills during the prison to be able to suck themselves after coming out of prisons.